2018
DOI: 10.1111/ceo.13385
|View full text |Cite
|
Sign up to set email alerts
|

Retinal imaging including optical coherence tomography angiography for detecting active choroidal neovascularization in pseudoxanthoma elasticum

Abstract: The systematic use of OCT, FA and OCT-A imaging can facilitate the diagnostic accuracy for detection and follow-up of CNV activity in PXE. While structural OCT is of high value, especially when longitudinal follow-up images are available, FA and OCT-A data might contribute to diagnostic accuracy in more complex cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…The ocular phenotype is characterized by so-called peau d'orange which marks the transition zone between the centrally calcified and peripheral uncalcified Bruch's membrane, peripheral chorioretinal atrophic spots (comet lesions), and angioid streaks which represent breaks within the thickened and brittle Bruch's membrane [5][6][7]. At later stages, macular atrophy may develop, or the disease course may be complicated by choroidal neovascularizations (CNV) that typically originate from angioid streaks [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The ocular phenotype is characterized by so-called peau d'orange which marks the transition zone between the centrally calcified and peripheral uncalcified Bruch's membrane, peripheral chorioretinal atrophic spots (comet lesions), and angioid streaks which represent breaks within the thickened and brittle Bruch's membrane [5][6][7]. At later stages, macular atrophy may develop, or the disease course may be complicated by choroidal neovascularizations (CNV) that typically originate from angioid streaks [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Birtel et al found that OCT shows a higher diagnostic accuracy of CNV in PXE than OCT angiography and FA, especially with longitudinal follow-up images, and FA and OCT angiography might contribute to the diagnostic accuracy in more complex cases. The systematic use of OCT, OCT angiography, and FA may facilitate the diagnosis and monitoring of AS-related CNV in PXE [31]. Furthermore, in PXE, the transition from classic retinal dystrophies to systemic disease with a retinal phenotype could be indistinct and requires careful observations, as noted previously [1,12].…”
Section: Discussionmentioning
confidence: 95%
“…Unfortunately, fluorescence angiography was not available to detect leakage of CNV. We believe that this should not be a problem, because angiography does not add information regarding CNV activity in PXE patients in most cases [15]. CNV activity was diagnosed if at least one of the following criteria was present: 1) hemorrhage in posterior pole on color fundus photography and/or 2) one or more intraretinal cysts of >50 μm diameter and/or subretinal fluid of >200 μm width, with signs of a CNV nearby, and/or 3) obvious growth of a subretinal neovascular complex.…”
Section: Assessment Of Outcomementioning
confidence: 99%